“How Does The Never To Be Differ From What Never Was?”: The Importance of Dreams and Memory in The Road - Barbieri, Diogo (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
The haunting presence of memories and dreams from an unregenerate past society thoroughly permeate the action of Cormac McCarthy’s vision of the post-apocalypse in The Road. Besides the intention of contrasting the barrenness of the world that the protagonists inhabit with the lively imagery of the old world, the recollections that invade the father’s inner self provide a clash between personal and collective narratives which push him to struggle for survival and protect his son in an effort to “carry the fire” of humanity. Parallelly, the symbolism of the dreams that we encounter throughout the novel hold valuable clues that can be accessed to resolve the ambiguous closure to The Road. In the first part of this paper, I will revisit the field of memory studies to reveal the importance that memory holds as a provider of meaning for life in the apocalypse. The second part of the article develops a theory that absolutely disregards any optimistic reading of the end of the novel, as it presents us with the possibility that what we read in the last pages of the book constitutes the wish-fulfilment produced by the boy’s dying dream. To investigate this enticing theory that was furthered by Jacob M. Powning, I will assess this hypothesis through the lenses of Psychoanalysis. McCarthy’s interest in the psychoanalytic studies, and his fascination with the dream world will help to develop a pertinent proposition that seeks to ultimately resolve the enigmatic Deus Ex-Machina that closes the novel.